Mathematics, Reason & Religion - Leach, Javier (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
This paper will study the relationship between mathematics and religion from the perspective of reason and the role played by reason in human knowledge. Firstly, I will study the relationship between reason, logic and mathematics. From this starting point, I will study the relationship between reason and natural science and finally, I will draw some conclusions on the relationship between reason, philosophy and theology. The relationship between mathematics, reason and religion will be studied within the context of the global unity of human knowledge. This paper intends to explain how the ‘pure deductive reason’ is present in all human thinking. Mathematics and natural science share this universal presence with metaphysics and religion. Pure deductive reasoning is somehow an absolute value that transcends all aspects and levels of human knowledge, including metaphysical and religious knowledge. Metaphysical and theological arguments need to be able to span different cultural communities. Pure deductive reasoning is a kind of reasoning that can fully span communities and it forms a basis for interdisciplinary, inter-cultural and inter-religious communication.